Taxonomic novelties in Plantago section Virginica (Plantaginaceae) and an updated identification key - Hassemer, Gustavo; Trevisan, Rafael; Meudt, Heidi; Rønsted, Nina (Phytotaxa, 2015)
This study raises two rather poorly understood subspecies to the rank of species, and revalidates two subspecies in Plantago (Plantaginaceae) section Virginica. Plantago napiformis, formerly P. tomentosa subsp. napiformis, is an uncommon species from grasslands in northeastern Argentina, southern Paraguay and southern Brazil. Plantago pretoana, formerly P. australis subsp. pretoana, is a rare species, endemic to high-elevation bogs in two small areas in southern Brazil: Serra do Itatiaia, and around Lagoa Dourada. Plantago australis subsp. angustifolia and P. australis subsp. hirtella have been recently synonymised under P. australis subsp. australis, but we present evidence here for the revalidation of these two subspecies. We also revise the distribution of P. australis subsp. angustifolia, greatly reducing it, and expand the distribution of P. australis subsp. australis. Finally, we provide an updated identification key to all 22 Plantago species and subspecies in Brazil, Paraguay, Uruguay and northeastern Argentina.